Cardiovascular Admissions, Readmissions, and Transitions of Care - Chang, Anna Marie (2014)
Hospital 30-day readmissions have become a major priority for hospitals. Hospitals face penalties for excessive readmissions for acute myocardial infarction (AMI) and heart failure (HF). Thus, it is important for hospitals to understand the transitions of care that occur for both of these conditions, and what tools are available to guide the processes involved. A multi-disciplinary team including Emergency Medical Service providers, Emergency Medicine providers, cardiologists, hospitalists, pharmacists, nurses, case managers, and outpatient physicians can all be involved in the process of safely transitioning a patient between care settings. Small-scale studies in the geriatric population have shown improved transitions of care and decreased readmissions with these care teams. The emergency department is a key transition point for patients with AMI and HF, yet it is rarely identified and utilized as such in transitions of care interventions. Future research and implementation projects will need to refine and expand the role of the emergency department in the process.